Pengaruh ROA dan ROE terhadap Return Saham pada Perusahaan Emiten Syariah di Bursa Efek Indonesia - Prakoso, Yoga Rizky; Ghani, Wan Ruslan Abdul; Riani, Novi (Jurnal Ekonomi Syariah dan Pariwisata Halal, 2025)
Islamic Issuers are Islamic companies that are members of the IDX. Islamic Issuers here consist of Banking, Insurance and Hotel companies. Stock returns are the rate of return or yield from shares invested by investors by issuers or companies. Signals indicate a relationship between profitability and stock returns. Profitability can be proxied by ROA and ROE. This study aims to determine the effect of ROA and ROE on stock returns. The research method uses quantitative associative. The population consists of 7 Islamic Issuers in the 2021-2023 launch year as research objects so that 21 samples are obtained. The analysis technique is multiple linear regression with panel data. The results of the study Prob Variable X2 or ROE obtained 0.0007 <0.05, so there is an effect of ROE on Stock Returns. The higher the ROE, the higher the Stock Return. Prob Variable X2 or ROE obtained 0.0007 <0.05, so there is an effect of ROE on Stock Returns. The higher the ROE, the higher the Stock Return.